Threats to sustainable utilization of wetland resources in Zimbabwe: a review - Musasa, Tatenda; Marambanyika, Thomas (Springer, 2021)
Wetlands are some of the most productive natural ecosystems in Zimbabwe as they provide a wide range of goods and services. The article examines spatial and temporal changes in wetland utilization patterns as well as threats to these fragile ecosystems and proffers suggestions to achieve sustainable use of wetlands. Literature on wetland use shows that cultivation (73%) and livestock grazing (36%) are the dominant wetland use activities in Zimbabwe. Combined with urban housing development, these land uses are the biggest contributors to wetland degradation and loss. About 57% and 27% of wetlands are in the moderately and severely degraded categories respectively. However, the effect of land uses, especially cultivation, on wetland ecology, is heterogeneous. Livestock grazing changes vegetation structure and composition and, ultimately, disturbs the wetland’s hydrology. Settlement establishment results in the disappearance of the wetland ecosystem. Considering that the two dominant land uses, cultivation and livestock grazing, are cornerstones of rural economies, there is need for further research to understand spatial variations on the impacts of similar land uses on different wetland types in different geographical settings. Therefore, further research should be done to understand the sustainability of human land uses on different wetland types, depending on their hydrogeomorphic characteristics, in order to continually promote sustainable development of the dependent societies.